Cellular hyperviscosity as a cause of neurological symptoms in leukaemia. Issue 6111 (25th February 1978) - Preston, F E; Sokol, R J; Lilleyman, J S; Winfield, D A; Blackburn, E K
Abstract : Six patients with various forms of leukaemia had neurological signs and symptoms associated with an extremely high white blood cell count and increased whole blood (but not plasma) viscosity. All were treated by leucapheresis with an Aminco Celltrifuge. Rapid and complete reversal of all symptoms occurred in three patients and partial recovery in one. One patient died shortly after leucapheresis and another (from cerebral intravascular coagulation) two days later. It is concluded that a cellular hyperviscosity syndrome may cause neurological dysfunction in patients with extremely high white cell counts, and that leucapheresis, in carefully selected patients, can be an effective method of treatment.